Spermine Attenuates the Action of the DNA Intercalator, Actinomycin D, on DNA Binding and the Inhibition of Transcription and DNA Replication - Wang, Sheng-Yu; Lee, Yueh-Luen; Lai, Yi-Hua; Chen, Jeremy J. W.; Wu, Wen-Lin; Yuann, Jeu-Ming P.; Su, Wang-Lin; Chuang, Show-Mei; Hou, Ming-Hon (PLOS ONE, 2012)
The anticancer activity of DNA intercalators is related to their ability to intercalate into the DNA duplex with high affinity, thereby interfering with DNA replication and transcription. Polyamines (spermine in particular) are almost exclusively bound to nucleic acids and are involved in many cellular processes that require nucleic acids. Until now, the effects of polyamines on DNA intercalator activities have remained unclear because intercalation is the most important mechanism employed by DNA-binding drugs. Herein, using actinomycin D (ACTD) as a model, we have attempted to elucidate the effects of spermine on the action of ACTD, including its DNA-binding ability, RNA and DNA polymerase interference, and its role in the transcription and replication inhibition of ACTD within cells. We found that spermine interfered with the binding and stabilization of ACTD to DNA. The presence of increasing concentrations of spermine enhanced the transcriptional and replication activities of RNA and DNA polymerases, respectively, in vitro treated with ActD. Moreover, a decrease in intracellular polyamine concentrations stimulated by methylglyoxal-bis(guanylhydrazone) (MGBG) enhanced the ACTD-induced inhibition of c-myc transcription and DNA replication in several cancer cell lines. The results indicated that spermine attenuates ACTD binding to DNA and its inhibition of transcription and DNA replication both in vitro and within cells. Finally, a synergistic antiproliferative effect of MGBG and ACTD was observed in a cell viability assay. Our findings will be of significant relevance to future developments in combination with cancer therapy by enhancing the anticancer activity of DNA interactors through polyamine depletion.